Keabsahan Pemberian Wasiat Berdasarkan Standarisasi Umur (Studi Komparatif Antara Kompilasi Hukum Islam dan Hukum Islam): The Validity of Granting a Will Based on Age Standardization (Comparative Study Between the Compilation of Islamic Law and Islamic Law) - St. Nurhalimah Hamka; Rosmita, Rosmita (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research was conducted with the aim of understanding the validity of wills based on age standardization from the perspective of the Compilation of Islamic Law and Islamic Law. Including to determine differences in the validity of wills based on age standards from the perspective of the Compilation of Islamic Law and Islamic Law. The type of research used is descriptive qualitative using normative literature and juridical study methods. As for the research results; Firstly, minor children who are not yet mature are allowed to make a will and their will is valid provided that the minor child must be of sound mind. In fact, the will of a small child has no legal basis from the Koran, except for the hadith narrated by Umar bin Khattab ra. that the will of a small child is permissible and is the word of a friend. Second, in the Compilation of Islamic Law it is very clear that a person who will make a will must be at least 21 years old, if the person doing it is not of age, in the Compilation of Islamic Law the will is invalid. Third, there is a difference between the Compilation of Islamic Law and Islamic Law, namely in determining the maturity and legal skills of the will. According to the Compilation of Islamic Law, a person who can make a will is a person who is truly an adult and has the ability to accept perfect laws. From what is seen in society, the age of 19 years is the standard for adulthood and the age of 21 years is the standard for making a will. As for Islamic law, the limits for people who make a will are based on being of age and being of sound mind.